Silence is not golden: investigating classroom participation anxiety among university students - Abdul Karim, Noor Harun; Ahamad Shah, Mohamed Ismail (IDOSI Publications, 2012, 2012)
Abstract: A phenomenon that prevails in university classrooms, particularly among the undergraduates, is their silent and reticent behaviors during classroom hours. This study was undertaken to test the hypothesis that such behaviors can be ascribed to what we have labeled as “classroom participation anxiety”, a type of situation anxiety not unlike communication apprehension. The population for this study comprised undergraduate students taking courses in “English for Occupational Purposes” in a university in Malaysia. The study investigated whether differences existed in classroom participation anxiety between male and female students; between local and international students; between students from the six bachelor degree programs. In addition, the study also investigated whether predictive relationships existed between perceived oral competence in English, students’ motivation to study, teachers’ verbal and non-verbal immediacy behaviors with classroom participation anxiety. The findings revealed that statistically significant differences existed between local and international students and between students from the six bachelor degree programs. However, no statistically significant mean differences existed in classroom participation anxiety between male and female students. The results also revealed that only two correlates were significantly predictive of classroom participation anxiety: perceived oral competence in English and teachers’ verbal immediacy behaviors. Key words: Classroom Participation Anxiety % Perceived Verbal and Non-verbal Immediacy Behaviours % Perceived Oral Competence in English % Internal Motivation